Chinese Traditional Cultural and Cross-Cultural Management - Shi, Zhibo (Vilnius University Open Series, 2021)
Confucian culture is an ancient culture that has been circulating in China for thousands of years. It represents the value of most Chinese people and plays an important role in Chinese history. From state governance to family management, Confucian culture has influenced all aspects of Chinese people, and, of course, has a great influence on the management of Chinese enterprise managers. However, cultural differences and conflicts when managing multinational teams are inevitable. Therefore, in this article, we will discuss Confucian culture and how to integrate it into modern enterprise management to solve the adverse consequences of cultural differences and conflicts, and discuss the drawbacks of Confucianism to modern enterprise management.